Clinical update of medications associated with QT prolongation among COVID-19 patients - Herbert, Ernest; Fournier, Dominique (The European Research Journal, 2022)
In the struggle against COVID-19 pandemic, chloroquine (CQ) (a 4-aminoquinoline) and its derivative hydroxychloroquine (HCQ) have both been used as a potential form of treatment among infected patients. Originally known as an antimalarial quinolone, many countries have adopted their use as an option to treat COVID-19 patients. In humans, dose-dependent chloroquine induces QT interval prolongation. It also blocks the human ether-a-go-go-related gene (hERG), which encodes the rapidly activating delayed rectifier K+ channel. The action potential duration is then prolonged, as the eventual QTc interval of the electrocardiogram (ECG), resulting in torsade de pointes and cardiac arrhythmias that could lead to sudden death. It is yet unknown whether COVID-19 itself has any effect on the QTc interval. The current review established what is new and different from other studies involving the use of chloroquine and hydroxychloroquine among COVID-19 patients plus the corresponding QT interval prolongation in affected individuals.